GREENHOUSE GAS EMISSIONS FROM POTATO CROP - Singh, Preeti (Potato Journal, 2022)
Human-produced gases including carbon dioxide (CO2), methane (CH4), and nitrous oxide (N2O) contribute to the natural greenhouse effect. The Intergovernmental Panel on Climate Change (IPCC) has concluded that immediate action is required to mitigate the severe risk of humaninduced climate change posed by these gases. According to the IPCC (2001) report, agriculture contributes approximately 4% of global carbon emissions from energy use. Agriculture produces emissions through a variety of processes, including enteric fermentation and animal waste disposal and fermentation, anaerobic process during rice cultivation, nitrification and de-nitrification linked to fertilisation, as well as land clearing, the burning of biomass, fuel wood, and agricultural waste.